MARCADORES PARASITOLÓGICOS E HEMATOLÓGICOS PARA A SELEÇÃO DE BOVINOS RESISTENTES À DERMATOBIOSE - PINTO, S. B.; THOMAZ-SOCCOL, V.; ROCHADELLI, R.; ANDRADE, R. R.; MONTANUCCI, C. R. (Archives of Veterinary Science, 2002)
O presente trabalho foi desenvolvido na UFPR - Campus Palotina e em três propriedades rurais do município de Palotina, Paraná, durante o período de setembro de 1997 a agosto de 1999. O experimento foi delineado com o objetivo de estudar possíveis marcadores (parasitológicos e hematológicos) que refletem a habilidade do gado de leite (raça Holandesa Preto e Branco) em resistir à parasitose por larvas de Dermatobia hominis (Linnaeus Jr., 1781). Um total de 1050 larvas de D. hominis foram expulsas por meio de compressão digital. Os maiores valores de contagem total de leucócitos foram observados nos animais que apresentaram o menor número de nódulos de larvas de D. hominis. Study of parasitological and hematological markers for the selection of dermatobiose resistant bovines Abstract The present research work has been carried out from September 1997 through August 1999 at Federal University of Paraná Palotina Campus and in three farms from the same County. The main aim of this study was to analyze the possible parasitological and hematological markers that reflect Black and White Holstein dairy cattle resistance towards parasitism by Dermatobia hominis (Linnaeus Jr, 1781) larvae. From the group of 14 experimental animals a total of 1050 D. hominis were collected by manual compression during the period of time of the experiment. From the hematological data it was possible to conclude that there was an inverse relationship between the total leucocytes counting values and the number of larvae nodules, so that the highest the number of leucocytes per l of blood, the lowest the number of larvae nodules.